A B1 flame-retardant grade silane crosslinked low-smoke halogen-free flame-retardant polyolefin insulation material and its preparation method
Developing low-smoke, halogen-free flame-retardant polyolefin insulating material with B1 flame retardant grade through silane cross-linking technology, solving the problems of limited types of wire and cable materials and complex production processes in the existing technology, and realizing the expansion of product types and production processes. Simplify, improve product stability and comprehensive performance.
Patent Information
- Application Number
- CN202411547762.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-01
- Publication Date
- 2025-02-11
- Estimated Expiration
- 2044-11-01
AI Technical Summary
In the prior art, there are limited types of wire and cable materials that meet the B1 flame retardant grade, the irradiated crosslinking products have complex processes and high costs, and the crosslinking stability of ultraviolet crosslinking products is insufficient.
Using silane crosslinking technology to develop a low-smoke, halogen-free, flame-retardant polyolefin insulating material with B1 flame retardant grade. Through carefully designed formulas and ratios of A and B materials, the silane crosslinking effect is achieved, simplifies production process and improves the product. stability.
It effectively expands the product types of wire and cable materials, simplifies production processes, reduces processing costs, improves the overall performance and stability of the product, and can be cross-linked and processed in black products.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of wire and cable materials, and in particular to a silane cross-linked low-smoke halogen-free flame-retardant polyolefin insulating material with a B1 flame-retardant grade and a preparation method thereof. Background Art
[0002] With the rapid and high-quality development of the wire, cable and cable material industry, the requirements for product functional levels are getting higher and higher. In recent years, with the implementation of the GB31247-2014 standard, the B1 flame retardant requirement has gradually become an important identification standard in the wire, cable and cable material industry, involving more and more product areas, and products that meet the B1 flame retardant grade requirements have become a rigid demand for industry development. At present, in the field of wiring, the products that meet the B1 grade requirements are mainly radiation cross-linked low-smoke halogen-free flame retardant polyolefin insulation, a small amount of UV cross-linked low-smoke halogen-free flame retardant polyolefin insulation, and a small number of product types. After the production of irradiation cross-linked products is completed, electron beam irradiation is performed again to achieve cross-linking. The process is complicated and the processing cost is high. The cross-linking stability of UV cross-linked products is poor, and black products cannot be cross-linked. Summary of the invention
[0003] The purpose of the present invention is to meet the requirements of industry standards and market development needs, expand the product categories of the industry, provide a B1 flame retardant grade silane cross-linked low-smoke halogen-free flame retardant polyolefin insulation material and a preparation method thereof, organically combine the B1 flame retardant function and the silane cross-linking technology, and develop a silane cross-linked low-smoke halogen-free flame retardant polyolefin insulation material that can meet the B1 flame retardant requirements.
[0004] The present invention adopts the following technical solution:
[0005] A B1 flame retardant grade silane cross-linked low-smoke halogen-free flame retardant polyolefin insulating material, the raw materials of the insulating material include material A and material B, and the weight ratio of material A to material B is 25: (5-6);
[0006] Wherein, the material A is prepared from the following raw materials in parts by weight:
[0007] 10-30 parts of ethylene-vinyl acetate copolymer;
[0008] Polyolefin elastomer 10-20 parts;
[0009] 2-10 parts of polyethylene;
[0010] 5-15 parts of polyolefin grafted material;
[0011] Flame retardant 110-160 parts;
[0012] 2-7 parts of lubricant;
[0013] 0.5-1.5 parts of compound antioxidant;
[0014] 0.06-0.12 parts of organic tin composite catalyst;
[0015] The flame retardant is a flame retardant system composed of magnesium hydroxide, aluminum hydroxide and phosphorus-nitrogen flame retardant; the phosphorus-nitrogen flame retardant is a combination of any three or more of melamine cyanurate, melamine polyphosphate, piperazine pyrophosphate and pentaerythritol polyphosphate;
[0016] The organic tin composite catalyst is a composition of dibutyltin dilaurate with a tin content of 15-18% and dibutyltin acetate with a tin content of 32%-34%, and the mass ratio of the two is 8:2;
[0017] The B material is prepared from the following raw materials in parts by weight:
[0018] 30-80 parts of ethylene-vinyl acetate copolymer;
[0019] 20-40 parts of polyolefin grafted material;
[0020] 1.5-2.5 parts of methylsilane;
[0021] Peroxide initiator 0.3-0.6 parts;
[0022] 0.5-1.5 parts of compound antioxidant.
[0023] The melt index of the ethylene-vinyl acetate copolymer added to the A material and the B material at 190°C and 2.16kg is (5-10) g / 10min;
[0024] The polyolefin grafted material is composed of one or more of maleic anhydride grafted polyethylene, maleic anhydride grafted EVA, and maleic anhydride grafted POE;
[0025] The composite antioxidant is composed of N, N'-bis[β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionyl] hydrazine, dilauryl thiodipropionate, pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate, and tris(2,4-di-tert-butylphenyl) phosphite.
[0026] The VA content of the ethylene-vinyl acetate copolymer added to the A material is 28-35wt%, and the VA content of the ethylene-vinyl acetate copolymer added to the B material is 18-28wt%;
[0027] The grafting degree of the polyolefin graft is (0.80-1.0) %.
[0028] The polyolefin elastomer added to the material A has a melt index of 5.0-10.0 g / 10 min at 190° C. and 2.16 kg;
[0029] The polyethylene has a melt index of 3.0-4.0 g / 10 min at 190° C. and 2.16 kg;
[0030] The lubricant comprises the following components in parts by weight: 3-5 parts of silicone masterbatch, 0.25-0.5 parts of polyethylene wax, and 0.2-0.4 parts of ethylene bis stearic acid amide.
[0031] The polyolefin elastomer is an ethylene-octene copolymer of 8 carbon atoms;
[0032] The silicone content of the silicone masterbatch in the lubricant is more than 50%.
[0033] Preferably, the phosphorus-nitrogen flame retardant is a composition of piperazine pyrophosphate, melamine polyphosphate, pentaerythritol polyphosphate and melamine cyanurate, with a mass ratio of 20:5:(2-5):5; or,
[0034] The phosphorus-nitrogen flame retardant is a composition of piperazine pyrophosphate, pentaerythritol polyphosphate and melamine cyanurate, and the mass ratio thereof is 25:(3.5-6):5.
[0035] The methylsilane added to the material B is vinyltrimethoxysilane with a content of more than 99%;
[0036] The peroxide initiator is dicumyl peroxide.
[0037] A method for preparing the B1 flame retardant grade silane cross-linked low-smoke halogen-free flame retardant polyolefin insulating material, comprising the preparation of material A, the preparation of material B, and uniformly mixing material A and material B according to a ratio to obtain the B1 flame retardant grade silane cross-linked low-smoke halogen-free flame retardant polyolefin insulating material;
[0038] Wherein, the preparation method of material A comprises the following steps:
[0039] S1-1. Weigh various raw materials according to the formula, pour them into an internal mixer and mix them evenly, then extrude and granulate them using a single screw extruder to obtain material A;
[0040] The preparation method of the B material comprises the following steps:
[0041] S2-1. Weigh various raw materials according to the formula, and then mix them at high speed in a kneading pot heated to 50°C. At the same time, add methyl silane and peroxide initiator, mix at high speed for 5 minutes, and then feed the materials into a twin-screw extruder for extrusion;
[0042] S2-2, the strips extruded in step S2-1 are drawn and pelletized through a water tank, and the pellets are first pumped into a 60°C hot air dryer for drying for 1-2 hours, then pumped into a cold air dryer for drying for 1 hour, and then packaged in a vacuum aluminum-plastic composite bag to obtain material B.
[0043] In the preparation step S1-1 of material A, the temperature of the internal mixer is 160°C, that is, when the internal mixing temperature of the product reaches 160°C, it is sent to the single screw extrusion granulation. The temperature of each zone during the single screw extrusion granulation is: 130°C in zone I, 130°C in zone II, 140°C in zone III, 150°C in zone IV, and 150°C in the head zone.
[0044] In the preparation step S2-1 of material B, the temperatures of each zone of the twin-screw extrusion granulation are: 50°C in zone I, 60°C in zone II, 70°C in zone III, 140°C in zone IV, 145°C in zone V, 150°C in zone VI, 155°C in zone VII, 160°C in zone VIII and 160°C in the die head zone.
[0045] Compared with the prior art, the technical solution of the present invention has the following advantages:
[0046] A. Currently, there are limited types of products on the market that meet the B1 flame retardant grade, mainly radiation cross-linking and UV cross-linking materials, but there are problems such as complex procedures, high costs, and poor cross-linking stability. The present invention provides a new type of product - silane cross-linked low-smoke halogen-free flame-retardant polyolefin insulation material through innovative technical combinations, which effectively expands the product types in the industry. Compared with radiation cross-linked products that require an additional electron beam irradiation process, the silane cross-linked material of the present invention does not require this step during the production process, which simplifies the production process and reduces processing costs. At the same time, it overcomes the problem of insufficient cross-linking stability of UV cross-linked products and improves the overall performance and stability of the product.
[0047] B. Through the carefully designed formula and ratio of material A and material B, the insulating material of the present invention can achieve a good silane cross-linking effect, and can be cross-linked even in black products, thereby broadening the application range of the product.
[0048] C. A variety of functional additives, such as flame retardants, lubricants, composite antioxidants, etc., are added to the formula of the present invention, which effectively improves the flame retardancy, processing performance and long-term stability of the material, so that the final product has more excellent comprehensive performance. DETAILED DESCRIPTION
[0049] The present invention can be implemented in many different forms and should not be construed as being limited to the embodiments set forth herein. Instead, these embodiments are provided so that the present disclosure will be thorough and complete and will fully convey the concept of the present invention to those skilled in the art. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative work are within the scope of protection of the present invention. Example 1
[0050] Material A was prepared according to the following formula (parts by weight):
[0051] Ethylene-vinyl acetate copolymer 20;
[0052] Polyolefin elastomer 12;
[0053] Polyethylene 2;
[0054] Maleic anhydride grafted POE 10;
[0055] Synthetic magnesium hydroxide 80;
[0056] Aluminum hydroxide 30;
[0057] Phosphorus-nitrogen flame retardant 1 28;
[0058] Compound antioxidant 1.5;
[0059] Polyethylene wax 0.5;
[0060] Silicone masterbatch 5.0;
[0061] Organic tin composite catalyst 0.1.
[0062] The components and mass fractions in the phosphorus-nitrogen flame retardant 1 in Example 1 are: piperazine pyrophosphate: melamine polyphosphate: pentaerythritol polyphosphate: melamine cyanurate = 16:4:4:4; the organic tin composite catalyst includes dibutyltin dilaurate with a tin content of 15-18% and dibutyltin acetate with a tin content of 32-34%, and the mass fraction ratio is 0.08:0.02.
[0063] Preparation of material A: Weigh all raw materials according to the formula, pour them into the internal mixer and mix them evenly, then use the single screw extruder to granulate. The mixed materials must be strictly dried. Granulation can be carried out by hot cutting process, and the cut particles must be uniform in size.
[0064] Example 2
[0065] Material A was prepared according to the following formula (parts by weight):
[0066] Ethylene-vinyl acetate copolymer 20;
[0067] Polyolefin elastomer 12;
[0068] Polyethylene 2;
[0069] Maleic anhydride grafted POE 10;
[0070] Synthetic magnesium hydroxide 80;
[0071] Aluminum hydroxide 30;
[0072] Phosphorus-nitrogen flame retardant 1 28;
[0073] Compound antioxidant 1.5;
[0074] Polyethylene wax 0.5;
[0075] Silicone masterbatch 5.0;
[0076] Organic tin composite catalyst 0.1.
[0077] The components and mass fractions in the phosphorus-nitrogen flame retardant 1 in Example 2 are: piperazine pyrophosphate: melamine polyphosphate: pentaerythritol polyphosphate: melamine cyanurate = 17.5:4.375:1.27:4.375; the organic tin composite catalyst includes dibutyltin dilaurate with a tin content of 15-18% and dibutyltin acetate with a tin content of 32-34%, and the mass fraction ratio is 0.08:0.02.
[0078] Example 3
[0079] Material A was prepared according to the following formula (parts by weight):
[0080] Ethylene-vinyl acetate copolymer 25;
[0081] Polyolefin elastomer 20;
[0082] Polyethylene 2;
[0083] Maleic anhydride grafted POE 5;
[0084] Synthetic magnesium hydroxide 85;
[0085] Taixing Aluminum HT-205 30;
[0086] Phosphorus-nitrogen flame retardant 2 28;
[0087] Compound antioxidant 0.5;
[0088] Polyethylene wax 0.3;
[0089] Silicone masterbatch 4.0;
[0090] Organic tin composite catalyst 0.12.
[0091] The preparation method of material A is the same as that of Example 1.
[0092] The components and mass fractions in the phosphorus-nitrogen flame retardant 2 in Example 3 are: piperazine pyrophosphate: pentaerythritol polyphosphate: melamine cyanurate = 19.44: 4.67: 3.89; the organic tin composite catalyst includes dibutyltin dilaurate with a tin content of 15-18% and dibutyltin acetate with a tin content of 32-34%, and the mass fraction ratio is 0.096: 0.024.
[0093] Example 4
[0094] Material A was prepared according to the following formula (parts by weight):
[0095] Ethylene-vinyl acetate copolymer 25;
[0096] Polyolefin elastomer 20;
[0097] Polyethylene 2;
[0098] Maleic anhydride grafted POE 5;
[0099] Synthetic magnesium hydroxide 85;
[0100] Taixing Aluminum HT-205 30;
[0101] Phosphorus-nitrogen flame retardant 2 28;
[0102] Compound antioxidant 0.5;
[0103] Polyethylene wax 0.3;
[0104] Silicone masterbatch 4.0;
[0105] Organic tin composite catalyst 0.12.
[0106] The preparation method of material A is the same as that of Example 1.
[0107] The components and mass fractions in the phosphorus-nitrogen flame retardant 2 in Example 4 are: piperazine pyrophosphate: pentaerythritol polyphosphate: melamine cyanurate = 20.90:2.92:4.18; the organic tin composite catalyst includes dibutyltin dilaurate with a tin content of 15-18% and dibutyltin acetate with a tin content of 32-34%, and the mass fraction ratio is 0.096:0.024. Example 5
[0108] Material B was prepared according to the following formula (parts by weight):
[0109] Ethylene-vinyl acetate copolymer 80;
[0110] Maleic anhydride grafted EVA 20; 171 1.5;
[0112] DCP 0.3 ;
[0113] Compound antioxidant 0.5.
[0114] Preparation of material B: Weigh various raw materials according to the formula, and then mix them at high speed in a kneading pot heated to 50°C. At the same time, add methylsilane A171 and initiator DCP, mix at high speed for 5 minutes, and then feed the materials into a twin-screw extruder for extrusion. The extruded strips are stretched and pelletized through a water trough. The particles are first pumped into a 60°C hot air dryer for drying for 1 hour, and then pumped into a cold air dryer for drying for 1 hour, and then packed in a vacuum aluminum-plastic composite bag to obtain material B. Example 6
[0115] Material B was prepared according to the following formula (parts by weight):
[0116] Ethylene-vinyl acetate copolymer 30;
[0117] Maleic anhydride grafted EVA 40; 171 2.5;
[0119] DCP 0.6;
[0120] Composite antioxidant 1.5.
[0121] The preparation method of material B is the same as that of Example 5. Comparative Example 1
[0122] Material A was prepared according to the following formula (parts by weight):
[0123] Ethylene-vinyl acetate copolymer 20;
[0124] Polyolefin elastomer 12;
[0125] Polyethylene 2;
[0126] Maleic anhydride grafted POE 10;
[0127] Synthetic magnesium hydroxide 80;
[0128] Aluminum hydroxide 30;
[0129] Piperazine pyrophosphate 20
[0130] Melamine polyphosphate 4
[0131] Melamine cyanurate 4
[0132] Compound antioxidant 1.5;
[0133] Polyethylene wax 0.5;
[0134] Silicone masterbatch 5.0;
[0135] Organic tin composite catalyst 0.1.
[0136] The organic tin composite catalyst comprises dibutyltin dilaurate with a tin content of 15-18% and dibutyltin acetate with a tin content of 32-34%, and the mass ratio is 0.08:0.02. Comparative Example 2
[0137] Material A was prepared according to the following formula (parts by weight):
[0138] Ethylene-vinyl acetate copolymer 25;
[0139] Polyolefin elastomer 20;
[0140] Polyethylene 2;
[0141] Maleic anhydride grafted POE 5;
[0142] Synthetic magnesium hydroxide 85;
[0143] Taixing Aluminum HT-205 30;
[0144] Piperazine pyrophosphate 24;
[0145] Melamine cyanurate 4;
[0146] Compound antioxidant 0.5;
[0147] Polyethylene wax 0.3;
[0148] Silicone masterbatch 4.0;
[0149] Organic tin composite catalyst 0.12.
[0150] The organic tin composite catalyst includes dibutyltin dilaurate with a tin content of 15-18% and dibutyltin acetate with a tin content of 32-34%, with a mass ratio of 0.096:0.024 Comparative Example 3
[0151] Material A was prepared according to the following formula (parts by weight):
[0152] Ethylene-vinyl acetate copolymer 20;
[0153] Polyolefin elastomer 12;
[0154] Polyethylene 2;
[0155] Maleic anhydride grafted POE 10;
[0156] Synthetic magnesium hydroxide 80;
[0157] Aluminum hydroxide 30;
[0158] Phosphorus nitrogen flame retardant system 1 28;
[0159] Compound antioxidant 1.5;
[0160] Polyethylene wax 0.5;
[0161] Silicone masterbatch 5.0;
[0162] Dibutyltin dilaurate 0.1.
[0163] The components and mass fractions in the phosphorus-nitrogen flame retardant 1 in Comparative Example 3 are: piperazine pyrophosphate: melamine polyphosphate: pentaerythritol polyphosphate: melamine cyanurate = 16:4:4:4.
[0164] Comparative Example 4
[0165] Material A was prepared according to the following formula (parts by weight):
[0166] Ethylene-vinyl acetate copolymer 25;
[0167] Polyolefin elastomer 20;
[0168] Polyethylene 2;
[0169] Maleic anhydride grafted POE 5;
[0170] Synthetic magnesium hydroxide 85;
[0171] Taixing Aluminum HT-205 30;
[0172] Phosphorus nitrogen flame retardant system 2 28;
[0173] Compound antioxidant 0.5;
[0174] Polyethylene wax 0.3;
[0175] Silicone masterbatch 4.0;
[0176] Dibutyltin silicate 0.12 in February.
[0177] The preparation method of material A is the same as that of Example 1.
[0178] The components and mass fractions of the phosphorus-nitrogen flame retardant 2 in Comparative Example 4 are: piperazine pyrophosphate: pentaerythritol polyphosphate: melamine cyanurate = 19.44: 4.67: 3.89;
[0179] The A material and the B material prepared above are mixed according to the following weight ratio:
[0180] The material A prepared in Example 1 and the material B prepared in Example 5 were mixed evenly in a ratio of 25:5;
[0181] The material A prepared in Example 2 and the material B prepared in Example 5 were mixed evenly in a ratio of 25:6;
[0182] The material A prepared in Example 3 and the material B prepared in Example 6 were mixed evenly in a ratio of 25:5;
[0183] The material A prepared in Example 4 and the material B prepared in Example 6 were mixed evenly in a ratio of 25:6;
[0184] The material A prepared in comparative example 1 and the material B prepared in example 5 were mixed evenly in a ratio of 25:5;
[0185] The material A prepared in comparative example 2 and the material B prepared in example 6 were mixed evenly in a ratio of 25:5;
[0186] The mixed material A and material B are extruded and coated on a cable conductor on a φ70 extruder to obtain a finished cable line. The performance tests are carried out according to the test standards listed in Table 1. The performance data are shown in the performance test results in Table 1.
[0187] Table 1 Performance test results of products
[0188]
[0189] The air oven thermal aging operation standard refers to GB / T 2951.12-2008.
[0190] The material A prepared in Example 1 and Example 2 are respectively mixed with the material B prepared in Example 5 to obtain the B1 grade silane cross-linked low-smoke halogen-free flame-retardant polyolefin insulation material; the material A prepared in Example 3 and Example 4 are respectively mixed with the material B prepared in Example 6 to obtain the B1 grade silane cross-linked low-smoke halogen-free flame-retardant polyolefin insulation material. The surface is very smooth and delicate, and all performances meet the standard requirements. The B1 test was carried out using a 2.5 square millimeter wire. The main test results show that the carbonization distance is less than 1.5 meters; the peak heat release rate is around 20kW; the total heat release is 6-8MJ; the smoke release rate is 0.01m 2 / s or so, and the d0 low dripping level can be achieved, which meets the standard requirements. The silane cross-linked low-smoke halogen-free flame-retardant polyolefin insulating material obtained by mixing the material A prepared in comparative example 1 with the material B prepared in example 5, and the silane cross-linked low-smoke halogen-free flame-retardant polyolefin insulating material obtained by mixing the material A prepared in comparative example 2 with the material B prepared in example 6 have a smooth surface. Except for the failure of the B1 level combustion test, other properties are qualified. The main test results show that the carbonization distance is greater than 1.5 meters, which is unqualified, and the heat release peak exceeds 30kW, which is unqualified; the total heat release is 11-13MJ, which meets the requirements and can reach the d0 dripping level. From the comparison of experimental results, the ratio of flame retardants, the content of organic tin catalysts and peroxide initiators are crucial to improving the flame retardant properties of the product. The addition of pentaerythritol polyphosphate is the key to the insulation material reaching the B1 flame retardant grade.
[0191] At the same time, the organotin catalyst system of the present invention can play a role in efficient catalytic cross-linking. Through the reasonable ratio of the two organotin catalyst systems, the catalytic efficiency is high, and natural cross-linking can be achieved quickly under the same environmental conditions. Specific data are shown in Table 2 below:
[0192] Table 2 Experimental results of catalytic cross-linking
[0193]
[0194] Currently, there are a limited number of products on the market that meet the B1 flame retardant grade, mainly radiation cross-linking and UV cross-linking materials, but there are problems such as complex processes, high costs, and poor cross-linking stability. The present invention provides a new type of product - silane cross-linked low-smoke halogen-free flame retardant polyolefin insulation material through innovative technical combinations, which effectively expands the product types in the industry. Compared with radiation cross-linked products that require an additional electron beam irradiation process, the silane cross-linked material of the present invention does not require this step during the production process, which simplifies the production process and reduces processing costs. At the same time, it overcomes the problem of insufficient cross-linking stability of UV cross-linked products and improves the overall performance and stability of the product.
[0195] Through the carefully designed formula and ratio of material A and material B, the insulating material of the present invention can achieve a good silane cross-linking effect, and can be cross-linked even in black products, thereby broadening the application range of the product.
[0196] A variety of functional additives, such as flame retardants, lubricants, composite antioxidants, etc., are added to the inventive formula, which effectively improves the flame retardant properties, processing properties and long-term stability of the material, making the final product have more excellent comprehensive performance.
[0197] Anything not described in the present invention is applicable to the prior art.
[0198] Obviously, the above embodiments are merely examples for the purpose of clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. However, the obvious changes or modifications derived therefrom are still within the scope of protection of the present invention.
Claims
1. A B1 flame retardant grade silane cross-linked low-smoke halogen-free flame retardant polyolefin insulation material, characterized in that: The raw materials of the insulating material include material A and material B, and the weight ratio of material A to material B is 25:(5-6); Wherein, the material A is prepared from the following raw materials in parts by weight: 10-30 parts of ethylene-vinyl acetate copolymer; Polyolefin elastomer 10-20 parts; 2-10 parts of polyethylene; 5-15 parts of polyolefin grafted material; Flame retardant 110-160 parts; 2-7 parts of lubricant; 0.5-1.5 parts of compound antioxidant; 0.06-0.12 parts of organic tin composite catalyst; The flame retardant is a flame retardant system composed of magnesium hydroxide, aluminum hydroxide and phosphorus-nitrogen flame retardant; The phosphorus-nitrogen flame retardant is a composition of piperazine pyrophosphate, melamine polyphosphate, pentaerythritol polyphosphate and melamine cyanurate, and the mass ratio thereof is 20:5:(2-5):5; or, The phosphorus-nitrogen flame retardant is a composition of piperazine pyrophosphate, pentaerythritol polyphosphate, and melamine cyanurate, and the mass ratio thereof is 25:(3.5-6):5; The organic tin composite catalyst is a composition of dibutyltin dilaurate with a tin content of 15-18% and dibutyltin acetate with a tin content of 32%-34%, and the mass ratio of the two is 8:2; The B material is prepared from the following raw materials in parts by weight: 30-80 parts of ethylene-vinyl acetate copolymer; 20-40 parts of polyolefin grafted material; 1.5-2.5 parts of methylsilane; Peroxide initiator 0.3-0.6 parts; 0.5-1.5 parts of compound antioxidant; The methylsilane added to the material B is vinyltrimethoxysilane with a content of more than 99%.
2. The silane cross-linked low-smoke halogen-free flame-retardant polyolefin insulation material with a flame retardant grade of B1 according to claim 1, characterized in that: The ethylene-vinyl acetate copolymer added to the A material and the B material has a melt index of 5-10 g / 10 min at 190° C. and 2.16 kg; The polyolefin grafted material is composed of one or more of maleic anhydride grafted polyethylene, maleic anhydride grafted EVA, and maleic anhydride grafted POE; The composite antioxidant is composed of N, N'-bis[β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionyl] hydrazine, dilauryl thiodipropionate, pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate, and tris(2,4-di-tert-butylphenyl) phosphite.
3. The silane cross-linked low-smoke halogen-free flame-retardant polyolefin insulation material with a flame retardant grade of B1 according to claim 2, characterized in that: The VA content of the ethylene-vinyl acetate copolymer added to the A material is 28-35wt%, and the VA content of the ethylene-vinyl acetate copolymer added to the B material is 18-28wt%; The grafting degree of the polyolefin graft is 0.80-1.0%.
4. The silane cross-linked low-smoke halogen-free flame-retardant polyolefin insulation material with a flame retardant grade of B1 according to claim 1, characterized in that: The polyolefin elastomer added to the material A has a melt index of 5.0-10.0 g / 10 min at 190° C. and 2.16 kg; The polyethylene has a melt index of 3.0-4.0 g / 10 min at 190° C. and 2.16 kg; The lubricant comprises the following components in parts by weight: 3-5 parts of silicone masterbatch, 0.25-0.5 parts of polyethylene wax, and 0.2-0.4 parts of ethylene bis stearic acid amide.
5. The silane cross-linked low-smoke halogen-free flame-retardant polyolefin insulation material with a flame retardant grade of B1 according to claim 4, characterized in that: The polyolefin elastomer is ethylene-octene copolymer; The silicone content of the silicone masterbatch in the lubricant is more than 50%.
6. The silane cross-linked low-smoke halogen-free flame-retardant polyolefin insulation material with a flame retardant grade of B1 according to claim 1, characterized in that: The peroxide initiator is dicumyl peroxide.
7. A method for preparing the B1 flame retardant grade silane cross-linked low-smoke halogen-free flame retardant polyolefin insulation material according to any one of claims 1 to 6, characterized in that: The method comprises the steps of preparing material A, preparing material B, and uniformly mixing material A and material B according to a ratio to obtain the silane cross-linked low-smoke halogen-free flame-retardant polyolefin insulating material with a flame retardant grade of B1; Wherein, the preparation method of material A comprises the following steps: S1-1. Weigh various raw materials according to the formula, pour them into an internal mixer and mix them evenly, then extrude and granulate them using a single screw extruder to obtain material A; The preparation method of the B material comprises the following steps: S2-1. Weigh various raw materials according to the formula, and then mix them at high speed in a kneading pot heated to 50°C. At the same time, add methyl silane and peroxide initiator, mix at high speed for 5 minutes, and then feed the materials into a twin-screw extruder for extrusion; S2-2, the strips extruded in step S2-1 are drawn and pelletized through a water tank, and the pellets are first pumped into a 60°C hot air dryer for drying for 1-2 hours, then pumped into a cold air dryer for drying for 1 hour, and then packaged in a vacuum aluminum-plastic composite bag to obtain material B.
8. The preparation method according to claim 7, characterized in that: In the preparation step S1-1 of material A, the temperature of the internal mixer is 160°C, that is, when the internal mixing temperature of the product reaches 160°C, it is sent to the single screw extruder for granulation. The temperature of each zone of the single screw extruder during extrusion granulation is: 130°C in zone I, 130°C in zone II, 140°C in zone III, 150°C in zone IV, and 150°C in the head zone.
9. The preparation method according to claim 7, characterized in that: In the preparation step S2-1 of material B, the temperatures of each zone of the twin-screw extruder for extrusion granulation are: 50°C in zone I, 60°C in zone II, 70°C in zone III, 140°C in zone IV, 145°C in zone V, 150°C in zone VI, 155°C in zone VII, 160°C in zone VIII and 160°C in the head zone.
Citation Information
Patent Citations
Silane crosslinking low-smoke halogen-free flame retardant polyolefin cable material with temperature-resisting grade of 125 DEG C and preparation method thereof
CN108129787A
Flame-retardant cable with self-extinguishing coating layer
US20220148760A1